Corporeidade e adolescência : estudo sobre a autoestima a partir das experiências vividas de alunos do ensino médio em escolas de Aracaju-SE - Silva, Markus de Lima (2018)
This dissertation aimed to describe the influence of the school context on the self - esteem of high school students from different schools in Aracaju, based on the narratives about coexistence and its unfolding in the corporeity. It is a study that seeks to approximate the contributions of phenomenology to the educational field, involving body experiences, intersubjective relationships and the manifestation of self-esteem in the adolescent's corporeity. We use as basis of theoretical support the foundations of Merleau-Ponty's phenomenological perspective, which seeks the understanding of the human being in his unit. The research was developed in two school institutions of Aracaju, one State Public School and another School of the Private Network of Education. Ten students from each school, aged between fourteen and eighteen, enrolled in the second year of high school, participated in this study. We used the qualitative approach of the research, since we consider it to be more appropriate to the type of research adopted, since its main characteristic is the descriptive knowledge that provides the interpretation of a context, as well as the discovery of new elements that may emerge during the process. We used as a methodological resource semi-structured interviews of the focal group type, where through the extension of the objective it was possible to contextualize the collected data even more and to establish a greater interaction among the investigated ones. Therefore, through interviews it was possible to understand that school is a place of multiple corporal experiences that act directly in the perception of adolescent world. His reports, generated by the discussions during the realization of the focus group, reveal that the corporal experiences and the intersubjective relations, are presented as determinants of the development of the individual, since it is in adolescence that the crises and the uncertainties about oneself proliferate. In this way, the school must affirm itself as an institution that truly enables integral human formation, where the coexistence between human beings is discussed, problematized and reflected from a broader approach that involves the corporeity of the adolescent. It is fundamental that self-esteem be included in educational objectives and principles, making it possible to understand that we are unique beings in the world, possessing potentialities different from each other, but that must be respected and valued by all.